2019
DOI: 10.1038/s41598-018-37245-8
|View full text |Cite
|
Sign up to set email alerts
|

Future N deposition and precipitation changes will be beneficial for the growth of Haloxylon ammodendron in Gurbantunggut Desert, northwest China

Abstract: Evaluation of precipitation and nitrogen (N) deposition in desert ecosystems helps to elucidate the reaction of desert ecosystems to future environmental changes. An in-situ field experiment was established to examine the influence of a long-term enhanced precipitation and N deposition on the photosynthetic traits and physiological characteristics of Haloxylon ammodendron in the Gurbantunggut Desert, northwest China, throughout the growing season in 2014–2016. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…The earth has experienced substantial precipitation changes in the past five decades, and climate change models predict further changes in precipitation regimes, with increased annual precipitation in many regions (IPCC, 2007). Many studies have demonstrated that global climate change has caused a series of ecological consequences, such as those for plant production (De Boeck, Hiltbrunner, Verlinden, Bassin, & Zeiter, 2018;Zhao et al, 2019) or vegetation changes (Jiang, Bao, Guo, & Ndayisaba, 2017;Li, Chen, Li, Deng, & Fang, 2015). However, changes in the precipitation regime are not uniform and are complicated, revealing spatial and temporal variations that are difficult to study (Li, Zhang, et al, 2015;Walther et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The earth has experienced substantial precipitation changes in the past five decades, and climate change models predict further changes in precipitation regimes, with increased annual precipitation in many regions (IPCC, 2007). Many studies have demonstrated that global climate change has caused a series of ecological consequences, such as those for plant production (De Boeck, Hiltbrunner, Verlinden, Bassin, & Zeiter, 2018;Zhao et al, 2019) or vegetation changes (Jiang, Bao, Guo, & Ndayisaba, 2017;Li, Chen, Li, Deng, & Fang, 2015). However, changes in the precipitation regime are not uniform and are complicated, revealing spatial and temporal variations that are difficult to study (Li, Zhang, et al, 2015;Walther et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in precipitation can significantly affect seed productivity and phenology, especially in harsh environments (Chen et al, 2019). Researchers have found that although decreases in precipitation suppress the aboveground biomass of plant communities, net primary production (NPP) is significantly more sensitive to increased precipitation than to decreased precipitation, especially in arid and semiarid environments (Knapp & Smith, 2001;Zhao et al, 2019). Most experimental manipulations have been performed in perennial grasslands (Byrne, Adler, & Lauenroth, 2017;Dunnett et al, 1998), and the Central Asia arid area is one of the largest arid regions at middle latitudes, and includes approximately one-third of the arid lands and almost 90% of the temperate deserts worldwide (Lioubimtseva & Henebry, 2009), but research on the effects of precipitation changes on plant communities in this area are rare (Zhang, Li, Zhang, Zhang, & Chen, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subordinate function values were calculated, and average membership and cold resistance of different discus species were analyzed according to Zhang et al (2015) and Zhao et al (2019) Weights of various comprehensive indicators were calculated as: The D values of the different treatments were calculated as: Xi, Xmin, Xmax and W□ are the score, minimum score, maximum scores and importance (weight) of the ith comprehensive indicator, respectively; Pi is the contribution rate of the □th comprehensive indicator of various treatments of two species; D is the comprehensive evaluation value for adaptability.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the nutrient types and contents in the plant tissues have a considerable effect on the rodents’ growth and development. Haloxylon ammodendron , representing the most widely distributed vegetation in desert areas, plays an important ecological role in maintaining the stability of sand dunes, providing essential nutrient and water conditions for other vegetation demonstrating undergrowth, and maintaining arid ecosystem function and structure (Mares et al, 1997; Zhao et al, 2019). The great gerbil ( Rhombomys opimus )—a main, highly social rodent in the desert and semidesert areas of Northwest China—is widely distributed in H. ammodendron forests (Wen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%